Enhancing Gross Motor Skills through Competition-Based Obstacle Play: An Effectiveness Study at TK Khadijah Surabaya - Aprilia Putri Tamala; Fikri Nazarullail; Siti Fadjryana Fitroh; Angga Fitriyono; Eka Oktavianingsih Oktavianingsih (Program Studi Pendidikan Guru Pendidikan Anak Usia Dini, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Trunojoyo Madura, 2025)
Background of the study: Gross motor skills constitute one of the essential developmental domains in early childhood education. Their development is equally important as cognitive, social–emotional, and language development. Therefore, early childhood educators must possess the ability to design learning experiences that effectively stimulate children’s physical and motor development. However, learning activities targeting gross motor skills in many early childhood institutions remain limited, particularly in the use of structured, engaging, and competition-based play that can enhance children’s balance, agility, and strength. Aims and scope of paper: This study aims to examine the effectiveness of competition-integrated obstacle games in improving the gross motor skills of children aged 4–5 years at TK Khadijah Surabaya. Methods: This study employed a quantitative approach using an experimental method. A pre-experimental design with a one-group pretest–posttest model was implemented. The sample consisted of 31 children in Group A at TK Khadijah Surabaya selected through a non-probability sampling technique. The instrument used was an observation sheet assessing three gross motor categories: balance, agility, and strength. Data analysis included prerequisite tests—normality and homogeneity—and hypothesis testing using a paired sample t-test. Reliability testing yielded a coefficient of 0.966, normality values were 0.130 (pretest) and 0.196 (posttest), and the homogeneity test produced a value of 0.217. Results: The paired sample t-test showed a significance value of 0.000 at alpha = 0.05, indicating a statistically significant difference between the pretest and posttest scores. The mean pretest score was 36.5, while the mean posttest score increased to 55.1, demonstrating that competition-based obstacle games effectively enhanced children’s gross motor development. Contribution: This study provides empirical evidence that competitive obstacle play can serve as an effective pedagogical strategy for stimulating gross motor development in early childhood. Practically, the findings offer guidance for early childhood educators in designing engaging, play-based learning activities that optimize children’s physical development in educational settings.